The Art of Change Movement: an anti-oppressive Social Work initiative - Matos-Silveira, Rosana; Cano, Yolanda; Mouton, Stéphanie (Cuadernos de Trabajo Social, 2016)
This article presents the Art of Change Movement (Movimiento Arte del Cambio), which has developed out of a project of the Association of Social Workers Without Boundaries (Asociación Trabajadores/as Sociales Sin Fronteras), with the collaboration of the Faculty of Social Work at Universidad de Granada and of education professionals, incorporating theatrical creativity and musical expression as pedagogical and social intervention tools. The aim is for the initiative to become another instrument in the fight against oppression. Through a laboratory for collective creativity involving students and professionals from social work and other social science disciplines, the movement seeks social transformation through artistic expression, based on political commitment and sustainable development that empowers participants.
Keywords: Social Work; music; theatre of the oppressed; social intervention; empowerment